Evaluation of the vector competence of a native UK mosquito Ochlerotatus detritus (Aedes detritus) for dengue, chikungunya and West Nile viruses. Issue 1 (December 2016) - Blagrove, Marcus; Sherlock, Ken; Chapman, Gail; Impoinvil, Daniel; McCall, Philip; Medlock, Jolyon; Lycett, Gareth; Solomon, Tom; Baylis, Matthew
Abstract Background To date there has been no evidence of mosquito-borne virus transmission of public health concern in the UK, despite the occurrence of more than 30 species of mosquito, including putative vectors of arboviruses. The saltmarsh mosquitoOchlerotatus detritus [syn.Aedes (Ochlerotatus )detritus ] is locally common in parts of the UK where it can be a voracious feeder on people. Methods Here, we assess the competence ofO. detritus for three major arboviruses: dengue virus (DENV), chikungunya virus (CHIKV) and West Nile virus (WNV) using adult mosquitoes reared from wild, field-obtained immatures. Results We demonstrate laboratory competence for WNV at 21 °C, with viral RNA detected in the mosquito's saliva 17 days after oral inoculation. By contrast, there was no evidence of laboratory competence ofO. detritus for either DENV or CHIKV. Conclusions To our knowledge, this is the first study to demonstrate competence of a UK mosquito for WNV and confirms thatO. detritus may present a potential risk for arbovirus transmission in the UK and that further investigation of its vector role in the wild is required.